La vulneración del principio de inocencia, por la inaplicación del articulo 624 en las contravenciones penales flagrantes. - Erazo, Darwin F. (2022)
This scientific article presents as its main objective the analysis of the violation of the presumption of innocence in the non-application of article 624 with respect to flagrant criminal offenses, being current and relevant in legal science, from the conception that the guarantees immersed in the Due process must be observed in all criminal offenses as expressed in the Constitution of the Republic and the Comprehensive Organic Penal Code. The present study has been carried out through the qualitative approach, with the level of descriptive research, applying the socio-legal, analytical-synthetic and inductive-deductive methods, for which the documentary analysis, case analysis and interview were carried out. obtaining the results and discussing to establish the conclusions. Establishing as a response to the formulated objectives, in flagrant criminal violations, the principle of innocence must be observed as a constituent element of the guarantee of due process, in compliance with article 624 of the COIP in which they expose the differentiation of following the process when it comes to of the elderly person or a pregnant woman, upon being apprehended immediately or within 24 hours of being presumed to be in flagrante delicto, their stay in a detention center is considered illegal.